DIGITAL STRATEGIES FOR STRENGTHENING TEACHER PROFESSIONAL COMPETENCE: A LITERATURE REVIEW AND CONCEPTUAL FRAMEWORK - Irfa'i Alfian Mubaidilla; Trias Fatih Mubaidilla (Universitas Citra Bangsa, 2025)
The advancement of digital technology presents both challenges and opportunities for the professional development of teachers, particularly in enhancing the quality of learning. This study aims to formulate an integrative digital strategy that supports the continuous strengthening of teachers competencies. The research employed a literature review with a qualitative approach, involving a systematic analysis of scholarly works related to pedagogical theories, educational technology, teacher competency frameworks (TPACK, DigCompEdu), and the concept of continuous professional development (CPD). Data were collected from journal articles, academic books, and relevant research reports, which were subsequently analyzed thematically to generate a new conceptual framework. The findings reveal that digital strategies such as digital pedagogy, blended learning, microlearning, artificial intelligence, big data, and digital professional learning networks significantly contribute to improving teachers pedagogical, technological, and professional skills. Furthermore, this study proposes a conceptual model consisting of Access, Training, Practice, Reflection, and Evaluation as a new design that is more responsive to real challenges, including time constraints, digital skills gaps, and teachers workload. These findings provide theoretical contributions by enriching the literature on digital based learning management, as well as practical implications for teachers, schools, and policymakers. Future research is recommended to empirically test the validity of this model through field studies and to explore broader implications for educational policy.